Pengaruh Inflasi dan Covid 19 terhadap Pasar Uang Antar Bank Syariah di Indonesi: - Ahmad Fatoni (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to analyse the effect of inflation and Covid 19 on the Islamic interbank money market and prove the validity of the fisher effect theory on the Islamic interbank money market in Indonesia. This study uses secondary data, namely time series data from the Islamic interbank money market and Inflation in Indonesia during the period January 2018 to November 2022. Meanwhile, the model used in this study is the Error Correction Model (ECM). The results showed that simultaneously in the long term and short term, inflation and Covid 19 variables had a significant effect on the Islamic interbank money market in Indonesia. Meanwhile, partially in the long term, the inflation variable has a positive and significant effect on the Islamic interbank money market. Covid 19 variable has a negative and significant effect on the Islamic interbank money market. In the short term, the Covid 19 variable has a negative and significant effect on the Islamic interbank money market in Indonesia. This study proves the existence of fisher effect on the Islamic interbank money market in Indonesia. Keywords: Islamic Interbank Money Market, Fisher Effect Theory, Covid 19